Electrophysiologic study for risk stratification in Brugada Syndrome: does it still matters?. (14th October 2021) - Faia Carvalho Dias, G; Oliveira, M; Faria, B; Von Hafe, P; Cardoso, F; Pereira, T; Tinoco, M; Ribeiro, S; Sanfins, V; Almeida, F; Lourenco, A
Abstract: Background: The value of eletrophisiologic study (EPS) with programmed ventricular stimulation for risk stratification in patients with Brugada Syndrome (BS) remains controversial. Purpose: The aim of this study is to determine the clinical and electrocardiographic predictors of positive EPS and to evaluate whether the induction of malignant ventricular dysrhythmias in the EPS is a predictor of events Methods: A retrospective study was carried out of patients with spontaneous type 1 Brugada pattern followed up in Arrhythmology consultation at our Hospital. From this population, patients who underwent EPS for stratification of dysrhythmic risk were selected. Clinical and electrocardiographic variables were analyzed. Hospital records and monitoring data from cardiac devices were consulted. Statistical analysis was performed using SPSS 20.0. Results: Fourty nine patients were included, with a mean age at the beginning of follow-up of 45±14 years, 40 (82%) of whom were male. In 16 individuals (33%) the EPS was positive with induction of malignant ventricular dysrhythmias. All patients with positive EPS implanted an implantable cardioverter-defibrillator and of the 32 patients with negative EPS, 10 implanted an implantable event recorder. The group of patients with positive EPS had a higher proportion of male patients (88% vs 78%). The median follow-up time was 31 months. The family history of sudden death, family history of BS, or identification of a genetic variant classified as pathogenic or probably pathogenic did not present any relationship with EPS positivity. Of the analyzed electrocardiographic markers, PR interval (178±29 vs 171±27) and QRS duration (119±24 vs 113±15) tended to be longer in patients with positive EPS. Additionally, it was found that 74% of patients with a QRS of less than 120 ms had a negative EPS. In the analysis of the value of EPS in the stratification of dysrhythmic risk, it was found that of all the patients who suffered events (4), 75% had positive EPS. Of the patients with negative EPS, only 3% (1) presented events in the follow-up. However, there was no significant association between these variables. Conclusion: In this population, the analysed clinical elements did not correlate with the EPS result. Although there was no statistical significance, there was a tendency for patients with narrower QRS to be more likely to have negative EPS. Accordingly with published data, it was found that the EPS result was not a predictor of events during the follow-up period, which highlights the difficulty of risk stratification in patients with BS. Funding Acknowledgement: Type of funding sources: None.